Mud Clam’s (Anodentia edentula) Density and Distribution Pattern in Kalangan Mangrove Forest Ecosystem - Susi Mei; Sayu Natio Tarihoran; Arsanti Arsanti; Rodhi Firmansyah; Dian Fitri M; Tengku Muhammad Ghazali; Daniel Sinaga (Jurnal Moluska Indonesia, 2021)
The excessive use of Mud Shells (Anodentia edentula) as a staple food by the people of Kalangan Village, Central Tapanuli Regency caused the decline of the shellfish population. This is marked by the scattering of mud shells at research sites and often people conduct shell-searching activities at low tide. Therefore, a scientific study is needed to know the density and distribution patterns as the basis for the possibility of cultivation activities, management of mud shell germplasm (Anodentia edentula), and mangrove ecosystems in kalangan area in the future optimally, sustainably, and sustainably. The study was conducted in September 2020, using the 1x1m2 transect method purposive sampling at low tide. The results showed that the density of Mud Shells (Anodentia edentula) amounted to 150 ind/m2 in Station I, 0 ind/m2 in Station II with distribution pattern clustering, and 43 ind/m2 in Station III with distribution pattern random. With the evidence that there is a research station that contain zero mud clam and with unsimilarity in distribution pattern that should be clustering in every research station, therefore it can be concluded that the abudance of mud clam in the ecosystem already decline both quantifically and qualitativelyand requires conservation and cultivation action to ensure its existence in the future.